Optimization of wheat debranning using laboratory equipment for ethanol production - George, Elizabeth; Rentsen, Bayartoghtok; Tabil, Lope G.; Meda, Venkatesh (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Ethanol production from starchy cereal grains is increasing rapidly due to increasing demand for alternative fuels. In Canada, wheat is the primary feedstock in ethanol plants. To improve the productivity of the ethanol plants in terms of product quality and yield, debranning of wheat grains may be employed. Debranning is advantageous in two ways. Firstly, bran removal increases the starch content of the feedstock, improving the fermentation efficiency of the ethanol plants. Secondly, bran, a valuable co-product can be used as an animal feed ingredient. In this study, experiments to optimize the debranning process were carried out using two kinds of abrasive equipment, the Satake and the TADD (tangential abrasive dehulling device) mills. Wheat samples (30 and 200 g) were debranned in the Satake mill at 1 215, 1 412, and 1 515 r/min rotational speeds, 30, 36, and 40 grit sizes, and 30, 60, and 90 s retention times, and in the TADD mill at 900 r/min rotational speed, 30, 36, 50, and 80 grit sizes, and 120, 180, 240, and 300 s retention times. In addition to debranning efficiency, the starch separation efficiencies of the two mills were calculated in different debranning conditions. In the Satake mill, the 30 g and 200 g sample size, 1 412 r/min and 1 515 r/min rotational speeds, all grit sizes, and 60 s of retention time demonstrated the highest debranning efficiency. Correspondingly, optimal results in the TADD mill were obtained with 200 g sample size, 900 r/min rotational speed, 50 and 80 grit sizes, and 180 s and 240 s retention times. However, based on the experimental results, Satake mill provided better debranning values compared to the TADD mill. The starch separation efficiency values supported these results. Keywords: wheat debranning, ethanol production, Satake mill, tangential abrasive dehulling device, grit size, retention time, rotational speed, starch separation efficiency DOI: 10.3965/j.ijabe.20140706.008 Citation: George E, Rentsen B, Tabil L G, Meda V. Optimization of wheat debranning using laboratory equipment for ethanol production. Int J Agric & Biol Eng, 2014; 7(6): 54－66.